IL‐1β mediating high mobility group box protein‐1 expression in condylar chondrocyte during temporomandibular joint inflammation. (16th December 2015) - Li, Cheng; Cai, Hengxing; Meng, Qinggong; Feng, Yaping; Guo, Huilin; Fang, Wei; Long, Xing
Abstract : Background: Temporomandibular joint (TMJ) osteoarthritis(OA)characterized with cartilage degen‐eration is associated with inflammation. High mobility group box chromosomal protein‐1(HMGB‐1)is a potent mediator of inflammation and the trigger of OA. The expression of HMGB‐1 in TMJ OA was uncovered, but the role of HMGB‐1 in TMJ cartilage degeneration is not fully understood. In this study, the regulation of HMGB‐1 in TMJ condylar cartilage was revealed. Methods: A complete Freund's adjuvant (CFA)‐induced TMJ inflammation animal model was employed and the expression of HMGB‐1 was detected at 1st, 2nd, and 6th weeks by immunohistochemistry. TMJ condylar chondrocytes were incubated with IL‐1β (10 and 40 ng/ml) at 24, 48, and 72 h, and the translocation and protein level of HMGB‐1 were evaluated by immunofluorescence and Western blot. Result: Nuclear HMGB‐1 staining was predominantly located in chondrocytes of both the fibrosis and proliferative zones in healthy TMJ. 1st week and 2nd week after CFA injection, immunoreaction could be detected in the cytoplasms of HMGB‐1‐positive cells and cartilage matrix especially in hypertrophic zone. At 6th week after CFA injection, cartilage matrix expression was disappeared and the cytoplasm expression of HMGB‐1 was very weak in hypertrophic zone. HMGB‐1 was translocated from the nucleus to the cytoplasm at 48 h after incubated with IL‐1β (10 ng/ml and 40 ng/ml). The protein level of HMGB‐1 was increased after stimulation and had a peak at 48 h. Conclusion: HMGB‐1 might be associated with TMJ inflammation and OA. Insight into the role of HMGB‐1 in TMJ inflammation is helpful to add the new knowledge into the pathogenesis of TMJ OA.